"Exposed and Vulnerable": Parent Reports of Their Child's Experience of Multidisciplinary Craniofacial Consultations. (October 2019) - Billaud Feragen, Kristin; Myhre, Anita; Stock, Nicola Marie
Objective: Childhood is a period of extensive socioemotional development, which can be impacted by the presence of a congenital craniofacial anomaly (CFA). Complex multidisciplinary treatment and long-term follow-up are normally required, yet understanding of children's treatment experiences is limited. The objective of this study was to investigate children's experiences of multidisciplinary team (MDT) consultations from the perspective of their parents. Design: Thirty-eight parents of children with a rare CFA were interviewed in person or over the telephone. Interviews were transcribed verbatim, translated into English, and explored using thematic analysis. Results: Background factors influencing the child's experience of the consultation included age, developmental stage, personality, and prior treatment experiences. Participants tried to prepare their child for meeting the MDT, but did not fully understand what to expect themselves. During consultations, participants were acutely focused on their child's emotional state, making it difficult to balance their desire to protect the child from potentially negative experiences, and the need to engage in a constructive dialogue with health professionals. Participants believed that health professionals' conduct could considerably influence the child's well-being and subsequent treatment decisions. Finally, participants highlighted the need to debrief their child to help them adjust positively. Conclusions: The ultimate goal of craniofacial care is to help children develop into confident adults who are able to cope with the challenges associated with their condition. Multidisciplinary teams play a vital role in creating a safe and supportive environment in which children feel genuinely informed and involved in key aspects of their care.